Social media use among the population after the COVID-19 pandemic - Magdalena Mazur; Klaudia Kister; Jakub Laskowski; Anna Szabrańska; Paulina Bronst; Julia Czechowska; Lidia Rosa; Monika Zach-Źródlak; Aleksandra Małolepsza; Natalia Rektor (Kazimierz Wielki University, 2023)
Introduction: With the development of new technologies and easier access to the Internet, the number of mobile devices is growing. According to statistics, in 2023, 5.18 billion people worldwide used the Internet, which was 64.6% of the world's population. The use of the Internet, including social media, has many health effects, such as Internet addiction. The COVID-19 pandemic has exacerbated this problem. Home quarantine and increasing social distance have clearly increased the level of emotional stress among humanity. Aim of the work: The aim of the work is to analyze the use of social media after the COVID-19 pandemic in Poland and the health consequences of this fact. Materials and methods: A proprietary online questionnaire was prepared, containing 19 questions. The survey was conducted in the Swietokrzyskie and Mazowieckie provinces from April 2023 to June 2023. 330 results were collected. The anonymity of participants taking part in the survey was preserved. Research results: The respondents included 219 women, accounting for 66.36%, and 111 men, 33.64% of the group. More than half of the respondents, 52.73%, believe that the COVID-19 pandemic has increased the amount of time spent on social media. The largest number of citizens, 153 (46.36%), spent between 2 and 4 hours a day on social media, while the smallest number, only 21 (6.36%), spent more than 6 hours a day. Only 13.64% of respondents log out of social media. 71.82% of respondents deny the statement that using social media in stressful moments can bring solace. Conclusions: This study proves the adverse impact of the COVID-19 pandemic on the frequency of social media use, causing its prolongation. Research also shows the growing problem of Internet addiction and its many health consequences. The problem mainly affects young people. It is important to conduct educational campaigns on the effects of Internet and social media addiction.